Síntese e caracterização de complexos de organoantimônio(V) com ácidos aminoidroxâmicos - Bruno Henrique Rodrigues do Prado (2015)
The leishmaniases are neglected diseases that affect endemically many countries, especially the less developed countries. Currently, the treatment of leishmaniasis is based essentially on chemotherapy. The first -line drugs are still pentavalent antimonials developed over 60 years ago. Such preparations have several limitations on clinical settings due to the long period and forms of administration, toxic effects and appearance of resistance. In the light of these limitations, the World Health Organization and others related entiti es strongly recommend and support the search of simpler and safer drugs, as well for oral and topical administration.Hydroxamic acid-containing compounds, -CONHOH, have been widely studied due to important role on biological systems, which is related to its ability to form metal complexes. They are present in siderophores, specific chelating agent for Fe(III), synthesized by microorganisms in order to solubilize and transport those ions into the cell. Hydroxamic acids are also known as constituent of growth factors, food additives, antibiotics, tumor inhibitors, antifungal agents and cell division factors.In the present work, it were synthesized six novel complexes of organoantimony(V) with the following hydroxamic acids derivatives from amino acids: -alaninehidroxamic acid, -methioninehidroxamic acid and -tryptophanehidroxamic acid. Three of them are 1:1 metal -ligand stoichiometry and the three others are 1:2 metal-ligand stoichiometry. Complexes were characterized by microanalyses, conductivity and pH measurements, infrared spectroscopy, ultraviolet spectroscopy, thermogravimetric analysis, solubility evaluation, melting point measurements and mass spectroscopy. The complexes exhibited wide range with respect to solubility, five of them are soluble in water and all of them are soluble in organic solvents, such dichloromethane. The Sb(Trpha)2 compound is a neutral complex, hence insoluble in water. Based on the results, we conclude that the ML complexes are cationic, with Cl as counter-ion, and the ML 2 complexes are anionic, with K + as counter-ion. It was proposed that the ligands are in enolic form when coordinated to the ion metal. For ML complexes, the coordination occurs via both deprotonated oxygen atoms, forming a five membered ring. For ML2 complexes, the coordination occurs only via deprotonated oxygen atom from the group oxime, C=NO-.